Prognostic Factors for Sustained Work Participation in Early Osteoarthritis: A Follow-Up Study in the Cohort Hip and Cohort Knee (CHECK) - Bieleman, Hendrik J.; Reneman, Michiel F.; Drossaers-Bakker, K. Wiepke; Groothoff, Johan W.; Oosterveld, Frits G. J. (Journal of occupational rehabilitation, 2013)
Objective To identify prognostic factors for the 2-year course of work participation in early osteoarthritis (OA) of hips or knees. Methods In this prospective cohort study, questionnaire data from 925 subjects was analyzed. Rate ratios were calculated to compare work participation with the general Dutch population, corrected for age, sex and education. The overall participation rate at T 2 was compared to baseline. Personal factors, self-reported health status (Western Ontario McMasters Arthritis Index—WOMAC), medical consumption and physical work demands were compared between subjects with sustained work participation and subject who stopped working; factors that differed significantly were included in a logistic regression analysis. Results Work participation in the cohort (mean age 58, 79 % females) decreased from 51 to 46 %, a similar rate to the general population. Subjects who continued working were younger than those who stopped working (mean 4.2 years) and they had less frequently reported sick-leave at baseline; the regression model included both factors. 11 % Of the workers reported sick-leave in the past year because of hip/knee complaints (similar to baseline). 20 % Reported work adaptations, compared to 14 % at baseline. Conclusion The 2-year course of work participation of people with early OA was similar to the general Dutch population. Sustained work participation was predicted by lower age, not by OA related factors.